Competition in the airlines : what is the public interest? - Daly, John Charles; Casey, Albert V.; American Enterprise Institute for Public Policy Research (Washington, D.C. : The American Enterprise Institute for Public Policy Research, 1977)
This book examines some of the competition in the airlines business and it effects on the citizenry. It further narrates sample application on how to provide healthy competition among airliners.
asm 05/03/2019
Loans
Keywords: Airlines; Aeronautics, Commercial